2009
DOI: 10.1186/alzrt5
|View full text |Cite
|
Sign up to set email alerts
|

Proteinopathy-induced neuronal senescence: a hypothesis for brain failure in Alzheimer's and other neurodegenerative diseases

Abstract: BackgroundAlzheimer's disease (AD) and a host of other neurodegenerative central nervous system (CNS) proteinopathies are characterized by the accumulation of misfolded protein aggregates. Simplistically, these aggregates can be divided into smaller, soluble, oligomeric and larger, less-soluble or insoluble, fibrillar forms. Perhaps the major ongoing debate in the neurodegenerative disease field is whether the smaller oligomeric or larger fibrillar aggregates are the primary neurotoxin. Herein, we propose an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 155 publications
(138 reference statements)
0
66
0
Order By: Relevance
“…Although the native conformation of αSYN in the human brain is still a topic of debate (Bartels et al 2011), the central region of αSYN (residues 61-95) constitutes the hydrophobic core of the protein, also known as the non-amyloid-β component of Alzheimer disease (NAC) domain, and this structural region allows αSYN to achieve a β-sheet-rich conformation that facilitates selfaggregation (Ueda et al 1994;Weinreb et al 1996;Hasegawa et al 2004;Matsuzaki et al 2004). Mounting evidence supports the general hypothesis that the accumulation of misfolded, aggregated proteins in the nervous tissues not only represents pathological hallmarks but also triggers a complex series of noxious events that result in neuronal degeneration (Golde and Miller 2009;Kikuchi et al 2010Kikuchi et al , 2016.…”
Section: Introductionmentioning
confidence: 89%
“…Although the native conformation of αSYN in the human brain is still a topic of debate (Bartels et al 2011), the central region of αSYN (residues 61-95) constitutes the hydrophobic core of the protein, also known as the non-amyloid-β component of Alzheimer disease (NAC) domain, and this structural region allows αSYN to achieve a β-sheet-rich conformation that facilitates selfaggregation (Ueda et al 1994;Weinreb et al 1996;Hasegawa et al 2004;Matsuzaki et al 2004). Mounting evidence supports the general hypothesis that the accumulation of misfolded, aggregated proteins in the nervous tissues not only represents pathological hallmarks but also triggers a complex series of noxious events that result in neuronal degeneration (Golde and Miller 2009;Kikuchi et al 2010Kikuchi et al , 2016.…”
Section: Introductionmentioning
confidence: 89%
“…These two different types of senescence have measurably distinct proteomes (text in blue) but share many major senescence phenotypes (text in red). Moreover, it has been shown that different factors are responsible for induction of these phenotypes (Aan et al, 2013;Braig et al, 2014;Chondrogianni and Gonos, 2004;Golde and Miller, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of senolytics on the progression of dementia could be tested in longer clinical trials (lasting months rather than weeks) because Alzheimer's disease and other dementias are associated with senescent cell accumulation at sites of brain pathology (reviewed in ref. 110). Of course, all these approaches would first need to be thoroughly vetted in proof-of-principle, preclinical studies in appropriate disease-specific animal models (preferably in old rather than young genetically modified animals, so that the aging tissue microenvironment is reproduced).…”
Section: Clinical Trials Strategiesmentioning
confidence: 99%